2017
DOI: 10.3168/jds.2016-11984
|View full text |Cite
|
Sign up to set email alerts
|

Economic effect of reducing nitrogen and phosphorus mass balance on Wisconsin and Québec dairy farms

Abstract: Our objective was to explore the trade-offs between economic performance (farm net income, FNI) and environmental outcomes (whole-farm P and N balances) of dairy farms in Wisconsin (WI; United States) and Québec (QC; Canada). An Excel-based linear program model (N-CyCLES; nutrient cycling: crops, livestock, environment, and soil) was developed to optimize feeding, cropping, and manure management as a single unit of management. In addition to FNI, P and N balances model outputs included (1) the mix of up to 9 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…Nitrogen mass balance did not vary widely across binary mixtures on both farms. Our study highlights and confirms previous findings of Pellerin et al (2017) and Hristov et al (2006), who reported that purchased concentrates and fertilizers influenced whole-farm P and N balances the most. When converted into kilograms per hectare (results not shown), the nutrient mass balances predicted in the present study for all binary mixtures tested fall within the wide range reported in previous studies conducted on dairy farms: 15 to 748 kg N ha −1 and −7 to 133 kg P ha −1 (Fangueiro et al, 2008;Hristov et al, 2006; Nielsen & Kristensen, T A B L E 7 Whole-farm P and N balances, and greenhouse gas (GHG) emissions on an annual basis of four alfalfa-grass binary mixtures on the southwestern Quebec (SWQ) and eastern Quebec (EQ) virtual dairy farms 2005; Soberon et al, 2015;Swensson, 2003).…”
Section: Eq Farmsupporting
confidence: 92%
“…Nitrogen mass balance did not vary widely across binary mixtures on both farms. Our study highlights and confirms previous findings of Pellerin et al (2017) and Hristov et al (2006), who reported that purchased concentrates and fertilizers influenced whole-farm P and N balances the most. When converted into kilograms per hectare (results not shown), the nutrient mass balances predicted in the present study for all binary mixtures tested fall within the wide range reported in previous studies conducted on dairy farms: 15 to 748 kg N ha −1 and −7 to 133 kg P ha −1 (Fangueiro et al, 2008;Hristov et al, 2006; Nielsen & Kristensen, T A B L E 7 Whole-farm P and N balances, and greenhouse gas (GHG) emissions on an annual basis of four alfalfa-grass binary mixtures on the southwestern Quebec (SWQ) and eastern Quebec (EQ) virtual dairy farms 2005; Soberon et al, 2015;Swensson, 2003).…”
Section: Eq Farmsupporting
confidence: 92%
“…The amount excreted and the characterization of manure are important variables in the context of nutrient management and the modeling of whole-farm economic and environmental performance (Pellerin et al, 2017;Uddin 2019). Holstein cows produced greater amounts of feces as-is (36%), urine as-is (14%), manure as-is (29%), feces DM (37%), and urine DM (20%) than did Jersey cows.…”
Section: Feces and Urinementioning
confidence: 99%
“…The situation is more complex with ruminant diets, where a large portion of feed intake is either grazed or stored forages, meaning that there is less control over the precise composition of the diet. While opportunities exist for reducing surplus P in ruminant diets without compromising livestock productivity, they may not generate the highest net farm income (Pellerin et al, 2017; Withers et al, 2015). …”
Section: Options For Mitigating Phosphorus Imbalancesmentioning
confidence: 99%